2022
DOI: 10.4149/neo_2022_211004n1408
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial lipase promotes acute myeloid leukemia progression through metabolic reprogramming

Abstract: Metabolic reprogramming occurs in the clonal evolution of acute myeloid leukemia (AML), which contributes to cell survival under metabolic stress and the development of drug resistance.Leukemic cells exhibit various metabolic profiles, which involve multiple metabolic pathways due to the heterogeneity of AML. However, studies on metabolic targets for AML treatment are mostly focused on glycolysis at present. In this work, we established conditional knock-in AML mouse models harboring Dnmt3aR878H/WT, NrasG12D/W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…The occurrence of metabolic reprogramming in the clonal evolution of AML can promote cell survival and drug resistance. Recent studies have shown that lipid metabolism and other metabolic abnormalities occur in AML mice, and the expression of endothelial lipase (LIPG) was increased in leukemia cells of AML mice, LIPG might be a potential target for the abnormal lipid metabolism in AML [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of metabolic reprogramming in the clonal evolution of AML can promote cell survival and drug resistance. Recent studies have shown that lipid metabolism and other metabolic abnormalities occur in AML mice, and the expression of endothelial lipase (LIPG) was increased in leukemia cells of AML mice, LIPG might be a potential target for the abnormal lipid metabolism in AML [ 48 ].…”
Section: Discussionmentioning
confidence: 99%